(untitled) (Journal of Oriental Studies, 2022)
TThe book of Al-Huruf (The Letters), as the most important philosophical works of Farabi in the philosophical study of language, refers to his precise philosophical thinking and is a reflection of the intellectual state of the Islamic world in the fourth century AH. The main purpose of this article is to find out why Farabi has studied language, word formation, language levels, and how language evolves in this work. A philosophical reading of the book Al-Huruf shows that ten centuries ago, Farabi›s linguistic meditations were closely linked to his ontology, as well as to the question of philosophy and religion. Unfortunately, so far research on Farabi›s thoughts about language has been based on a logical or linguistic approach. The scholars, disregarding Farabi›s philosophical approach to language, offered views that considered “Letters” to be merely a description of syntax or letters or words. In this article, in addition to explaining Farabi›s philosophical view of language, we seek to explore three fundamental issues: First, we will examine his intellectual foundations on the evolution of language. Second, we expound on the relationship between language with syntax and logic, which was the most important topic of the debate which occurred in 320 AH, and finally, we discuss the philosophical achievements of language to reveal the importance of Farabi›s linguistic thought, which has been neglected so far. Key words: Al-Farabi, Al-Huruf, language, logic, philosophical reading.